Anthelmintic resistance in gastrointestinal nematodes in sheep raised under mountain farming conditions in Northern Italy - Lambertz, Christian (Vet Rec Open, 2019)
Anthelmintic resistance (AR) in sheep raised under mountain farming conditions in South Tyrol (Northern Italy) was assessed on eight farms (n=99 animals). A faecal egg count reduction (FECR) test was done after routine anthelmintic treatments. Furthermore, on 27 farms (n=306 animals), a FECR test was conducted after oral formulations of a macrocyclic lactone (ML), benzimidazole (BZ) (partly in combination with salicylanilide (SA)) or a combination of imidazothiazole and SA were applied under controlled conditions on the same farm. Following routine treatments, three of five ML-treated flocks showed an adequate efficacy, while the other two reached a FECR of only around 75 per cent. A wide range of gastrointestinal nematode genera were identified in one flock following the treatment. From the three BZ-treated flocks, only one showed an adequate FECR, both other farms reached 68 per cent and 84 per cent, respectively. Under controlled conditions, FECR ranged between 77 per cent and 81 per cent indicating AR for all the applied anthelmintics. Trichostrongylus species, Teladorsagia species and Haemonchus species were identified after ML treatment, Teladorsagia species after BZ treatment and Trichostrongylus species and Haemonchus species after combined BZ and SA application. Taking into consideration that underdosing might have affected results of the routine treatments, a high prevalence of AR was found in sheep under mountain farming conditions.